COMPARATIVE ANALYSIS OF THE QUALITY OF LIFE OF PATIENTS DEPENDING ON THE METHOD OF AORTIC STENOSIS CORRECTION: TAVI VERSUS SAVR WITH A BIOLOGICAL PROSTHESIS - Todurov, Mykhailo; Zelenchuk, Oleg; Khokhlov, Andriy; Stan, Mykola; Ponych, Natalia; Sudakevych, Serhiy; Todurov, Borys (Eastern Ukrainian Medical Journal, 2024)
Introduction. The impact of transcatheter aortic valve replacement (TAVI) on health-related quality of life (QoL) is critical, especially for elderly patients who often prioritize quality of life over duration, but the QoL benefits of this technique have been largely unexplored . The purpose of this work was to conduct a comparative analysis of the quality of life of patients after correction of aortic valve stenosis using TAVI and surgical aortic valve prosthetics with a biological prosthesis. Materials and methods. Adult patients (over 18 years of age) who underwent primary surgical or transcatheter aortic valve replacement at the State Institution "Heart Institute of the Ministry of Health" between 2018 and 2022 are included in the study. Quality of life was assessed using the Medical Outcome Study Short Form-36 (SF-36) questionnaire one day before and 6 months after the procedure. The results. The study included 72 patients, of whom TAVI was performed in 47 (65.3 %) cases and SAVR with a biological prosthesis in 25 (34.7 %) cases. Patients with TAVI were older (p = 0.007) and characterized by a significantly higher level of operative risk according to EuroSCORE II (p < 0.001) compared to patients with SAVR. In TAVI patients, there was a significant improvement in all SF-36 parameters in the postoperative period compared to baseline values (p < 0.05), while parameters such as pain (p = 0.917) and mental health (p = 0.053 ) were not significantly different compared to baseline values in patients with SAVR biological prosthesis. Conclusions. The results of the assessment of the quality of life in the TAVI group at the end of the 6th month were characterized by a reliable increase in all indicators according to the SF-36 questionnaire, while in patients with SAVR, the dynamics of two indicators, such as mental health and pain, were recorded as unreliable.